Nationwide Seroprevalence of Dirofilaria immitis Antigen and Antibodies to Borrelia burgdorferi, Anaplasma spp., and Ehrlichia spp. in Shelter Cats in the United States, 2007–2011 - Rachel C. Smith; Lindsay A. Starkey; Joy V. Bowles; Jamie M. Butler; Jane Mount; Tracy M. Land; Byron L. Blagburn (Parasitologia)
Vector-borne infections persist as a significant issue in both human and animal health. Many of the most common vector-borne infections in the USA, especially tick-borne infections, are known to be zoonotic, including Lyme disease, anaplasmosis, and ehrlichiosis, and these infections may also negatively impact the health of infected animals. Convenient patient-side assays for the detection of antibodies to Borrelia burgdorferi, Anaplasma spp., and Ehrlichia spp., and antigen of Dirofilaria immitis have allowed for the generation of robust and large-scale prevalence data in dogs. Data of similar scale and distribution are not available in cats, and most feline prevalence studies have evaluated a small sample size with limited geographic distribution. The objective of this study was to evaluate the prevalence of antibodies to B. burgdorferi, Anaplasma spp., and Ehrlichia spp., and D. immitis antigen among shelter cats across the USA, a population that is presumably at high risk for ectoparasitism and, consequently, exposure to vector-borne infections. In total, 2232 whole blood samples were collected from shelter cats across four regions of the USA—South, Northeast, Midwest, and West—and were evaluated using the Idexx SNAP® 4Dx® Test. Ectoparasites were also opportunistically collected from cats during blood collection and morphologically identified. The prevalence of at least one vector-borne infection was 2.60%, and the nationwide prevalence was 1.88% for B. burgdorferi, 0.54% for Anaplasma spp., 0.09% for Ehrlichia spp., and 0.55% for D. immitis. A total of 1120 ectoparasites were collected from 423 cats, including 27 ticks and 1093 fleas. Although the overall prevalence of the pathogens in this survey is relatively low, we observe that there is an increased exposure risk regionally for some agents, with geographic distributions in this study mostly coinciding with established human and canine distributions. Understanding these findings in an assumed non-protected population of cats allows us to extrapolate the risk to pet cats if they are not provided routine veterinary care, including a broad-spectrum parasite prevention program.